PELATIHAN AKUNTANSI PERPAJAKAN KEPADA SISWA SMK CINTA KASIH TZU CHI DALAM MEMPERSIAPKAN KEBUTUHAN DUNIA KERJA - Subianto, Gladys Evelyn; Merry Susanti (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2024)
Taxes have an important role in supporting the country's economy by becoming the government's main source of income to finance development. In an increasingly complex world of work, Vocational High School (SMK) graduates are required to have a deep understanding of taxation. Tax accounting training activities are provided to vocational school students, especially at Cinta Kasih Tzu Chi Vocational School so that students are ready to face industry needs. Tax accounting training for Tzu Chi Cinta Kasih Vocational School students aims to improve students' understanding and skills in facing the increasingly complex demands of the world of work, especially in the field of taxation. This training was carried out for two months using conventional teaching methods, knowledge game methods, group discussions and collaboration. This training process focuses on mastering basic tax concepts, solving practical problems, and equipping students with skills according to industry needs. Students play an active role in guiding students with direction from teachers and supervisors. The results of the training show that Tzu Chi Love Love Vocational School students are able to develop a good understanding of taxation, although some students still need additional guidance. In addition, game-based learning methods have succeeded in increasing student interaction and interest in learning. This training provides a positive contribution not only for students, but also for students in honing their professional skills in the future. This program is expected to be able to bridge the gap between the educational curriculum in vocational schools and the dynamic needs of industry. ABSTRAK Pajak mempunyai peranan penting dalam menunjang perekonomian negara dengan menjadi sumber pendapatan utama pemerintah untuk membiayai pembangunan. Dalam dunia kerja yang semakin kompleks, lulusan Sekolah Menengah Kejuruan (SMK) dituntut untuk memiliki pemahaman yang mendalam mengenai perpajakan. Kegiatan pelatihan akuntansi perpajakan diberikan kepada siswa SMK khususnya di SMK Cinta Kasih Tzu Chi agar para siswa siap menghadapi kebutuhan industri. Pelatihan akuntansi perpajakan bagi siswa SMK Cinta Kasih Tzu Chi bertujuan untuk meningkatkan pemahaman dan keterampilan siswa dalam menghadapi tuntutan dunia kerja yang semakin kompleks khususnya di bidang perpajakan. Pelatihan ini dilaksanakan selama dua bulan dengan menggunakan metode pengajaran konvensional, metode permainan pengetahuan, diskusi kelompok dan kolaborasi. Proses pelatihan ini berfokus pada penguasaan konsep dasar perpajakan, pemecahan masalah praktis, dan pembekalan mahasiswa dengan keterampilan sesuai kebutuhan industri. Mahasiswa berperan aktif dalam membimbing siswa dengan arahan dari guru dan dosen pembimbing. Hasil pelatihan menunjukkan bahwa siswa SMK Cinta Kasih Tzu Chi mampu mengembangkan pemahaman perpajakan dengan baik, meskipun beberapa siswa masih memerlukan bimbingan tambahan. Selain itu, metode pembelajaran berbasis permainan berhasil meningkatkan interaksi dan minat belajar siswa. Pelatihan ini memberikan kontribusi positif tidak hanya bagi siswa, namun juga bagi mahasiswa dalam mengasah kemampuan profesionalnya di masa depan. Program ini diharapkan mampu menjembatani kesenjangan antara kurikulum pendidikan di SMK dengan kebutuhan industri yang dinamis